Circulating Markers of Interstitial Lung Disease and Subsequent Risk of Lung Cancer - Shiels, Meredith S. (2011)
BACKGROUND: Inflammation and pulmonary diseases, including interstitial lung diseases, are associated with increased lung cancer risk. Circulating levels of surfactant protein-D (SP-D) and Krebs von Lungren-6 (KL-6) are elevated in interstitial lung disease patients, and may be useful markers of processes contributing to lung cancer. METHODS: We conducted a nested case-control study, including 532 lung cancer cases, 582 matched controls and 150 additional controls with chest x-ray (CXR) evidence of pulmonary scarring, in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial. Serum SP-D and KL-6 levels were measured using enzyme immunoassay. Logistic regression was used to estimate the associations of SP-D and KL-6 with lung cancer and CXR scarring. RESULTS: Cases had higher levels than controls for SP-D (median 118.7 vs. 105.4 ng/ml, p-value=0.008) and KL-6 (372.0 vs. 325.8 μg/ml, p-value=0.001). Lung cancer risk increased with SP-D (p-trend=0.0003) and KL-6 levels (p-trend=0.005). Compared to the lowest quartile, lung cancer risk was elevated among those with the highest quartiles of SP-D (odds ratio [OR]=1.87; 95% confidence interval [CI] 1.32–2.64), or KL-6 (OR=1.58; 95% CI 1.11–2.25). Among controls, participants with CXR scarring were more likely than those without scarring to have elevated levels of SP-D (quartile 4 vs. quartile 1: OR=1.67; 95% CI: 1.04–2.70; p-trend=0.05) but not of KL-6 (OR=1.04; 95% CI: 0.64–1.68; p-trend=0.99). CONCLUSION: Circulating levels of SP-D and KL-6 are associated with subsequent lung cancer risk. IMPACT: Our findings support a potential role for interstitial lung disease in lung cancer etiology or early detection, but additional research is needed.